The Effect of Raw Material Mixture Composition and Adhesive Concentration on Candlenut Shell (Aleurites molucanna) and Empty Palm Fruit Bunches (Elaeis guineensis jack) Biobriquette Quality - Adrianto Prihartantyo; Yulisa Lestari; Aga Nugraha; Labora Roma (Department of Chemistry, Faculty of Sciences and Informatics, University of Jenderal Achmad Yani, 2026)
Biobriquettes serve as a renewable energy alternative with the potential to replace conventional charcoal while producing lower emissions. This study aimed to evaluate the effects of varying the ratio of raw material mixtures and the concentration of binder made from cassava starch on the quality of biobriquettes produced from candlenut shells (Aleurites moluccana) and empty palm oil fruit bunches (Elaeis guineensis jack). The selection of these raw materials was based on their abundant availability in Indonesia and their high lignocellulosic content. The biobriquettes were produced through a carbonization process, in which the candlenut shells were heated at 350°C for 30 minutes, while the palm oil empty fruit bunches were carbonized at 300°C for the same duration. The study applied variations in the composition ratios of candlenut shells to empty fruit bunches (100:0, 80:20, 60:40, 40:60, 20:80, and 0:100), as well as binder concentrations of 10%, 20%, and 30% (w/w) using cassava starch. The resulting biobriquettes were tested according to the Indonesian National Standard SNI 01-6235-2000 through proximate and physical analyses. The findings indicated that the variation.